EXPLORING STUDENTS’ OPINION ON THE IMPLEMENTATION OF LOCAL CULTURE BASED LEARNING IN TEACHING ENGLISH - Prayudha S, Joko (Universitas Aisyah Pringsewu, 2023)
Culture is an aspect of life that influences the mindset and habits of a population in a region. Culture is also an element that cannot be separated from a community's pattern of life, so it is very necessary to understand a culture in order to determine boundaries when carrying out an activity in everyday life. This study aims to examine students' perceptions of learning English based on local culture. Research using qualitative methods through a descriptive approach. Participants in this study consisted of 30 students who were studying English. Data were obtained through observation and interviews related to students' opinions when learning English through local culture-based learning. Data were analyzed through data reduction, data display, and conclusion. The results of the study show that students are highly motivated to understand English material related to local culture. In addition, students can more easily understand the material provided related to local culture and can be more confident when explaining their understanding and knowledge using English.